1868-69 N.C. Sess. Laws 96, 101-102 - (:unkn) unknown (My University, 1869)
Priv. Laws, ch. 79, § 25: The commissioners may prevent by penalties the firing of guns, pistols, crackers, gunpowder or other explosive materials in the streets or corporate limits.
Keywords: DISCHARGE